Research on the Impact of Environmental Regulation on Green Technology Innovation From the Perspective of Innovation Investment - Lingjun Guo; Chengliang Du; Wenyu Tan (SAGE Open)
Environmental regulation has emerged as an institutional response to the global ecological crisis, leading to discussions on its impact on green technology innovation. However, due to variations in indicator selection and data analysis, the academic community has yet to reach a consensus on this matter. To shed further light on the relationship between environmental regulation and green technology innovation, this study focuses on innovation investment in Chinese provincial regions from 2008 to 2019. By incorporating spatial econometrics, mediation effects, and threshold models, the study investigates the role of innovation investment in the influence of environmental regulation on the process of green technology innovation. The findings reveal the following: (1) The impact of environmental regulation on green technology innovation follows a non-linear “U-shaped” relationship. (2) Innovation investment acts as a mediator in the promotion of green technology innovation by environmental regulation, but this mediating effect exhibits stage-specific characteristics. (3) Environmental regulation has a threshold effect on the promotion of green technology innovation, with a more significant impact observed beyond the threshold value. Overall, these conclusions highlight the crucial role of innovation investment in driving the development of green technology innovation under environmental regulation.